Highly efficient and simultaneous removal of 2‐mercaptobenzothiazole and 2‐mercaptobenzoxazole from water samples by copper oxide nanoparticles. Issue 9 (25th February 2013) - Parham, Hooshang; Khoshnam, Farzaneh
Abstract: BACKGROUND: This study introduces a method for simultaneous removal of 2‐mercaptobenzoxazole (2MBO) and 2‐mercaptobenzothiazole (2MBT) from water samples. The method uses a cartridge loaded with copper oxide nanoparticles as an efficient adsorbent to separate these hazardous mercaptans from aqueous solutions in a flow process . RESULTS: The effects of some important parameters such as amounts of adsorbent, pH, buffer type and its volume, electrolyte concentration, contact time, flow rate, tolerable volume of solution, reusability of cartridges and interfering ions on removal efficiency were studied. Data on adsorption were analyzed using linear and non‐linear forms of first‐ and second‐order kinetic equations and also Langmuir and Freundlich isotherm models and results showed that maximum adsorption amounts of 90.9 mg g −1 and 158.7 mg g −1, were obtained for 2MBO and 2MBT, respectively . CONCLUSION: The proposed removal method is independent of pH level of the sample solution and is effective over a wide range of pH values. Using a copper oxide nanoparticle loaded cartridge (CONLC) has the advantage that there is no need to collect nanoparticles after the removal process and that CONLC can be reused for further removal processes (at least three times). This method was successfully applied to remove 2MBT (≥95% removal) from the cooling water of a 3000 MW power plant. © 2013 Society of Chemical Industry